1992
DOI: 10.1071/sr9920209
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activity and survival in soils dried at different rates

Abstract: The changes in microbial biomass C, soil respiration, microbial activity (respiration/microbial C) and the content of oxidizable organic C extracted by 0-5 M K2SO4, were measured in four soils of contrasting characteristics (a sand, two silt loam soils and a peat) which were air-dried at 22�C at three different rates in the laboratory. Respiration was also measured on samples of the drying soils rewetted with water. The rates of drying were: <10 h (fast), <33 h (medium) and <62 h (slow); drying was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…It is likely that our monthly sampling regime missed short-term nutrient pulses, although the absence of a broad increase in nutrient availability at the onset of the wet season provides some support for the suggestion that nutrient pulses are more common in dry tropical forests with a 6-mo dry season (Singh et al, 1989;Campo et al, 1998) than in semi-deciduous forests with a 4-mo dry season (Yavitt et al, 1993). This might occur because the length of the dry season influences the degree of deciduousness (and therefore the amount of litter fall in the dry season), as well as the degree of microbial desiccation and associated nutrient release at the end of the dry season (West et al, 1992).…”
Section: Discussion Seasonal Effects On Extractable Soil Nutrientsmentioning
confidence: 99%
“…It is likely that our monthly sampling regime missed short-term nutrient pulses, although the absence of a broad increase in nutrient availability at the onset of the wet season provides some support for the suggestion that nutrient pulses are more common in dry tropical forests with a 6-mo dry season (Singh et al, 1989;Campo et al, 1998) than in semi-deciduous forests with a 4-mo dry season (Yavitt et al, 1993). This might occur because the length of the dry season influences the degree of deciduousness (and therefore the amount of litter fall in the dry season), as well as the degree of microbial desiccation and associated nutrient release at the end of the dry season (West et al, 1992).…”
Section: Discussion Seasonal Effects On Extractable Soil Nutrientsmentioning
confidence: 99%
“…These finding may be related to microbial activity and populations. It was reported that soil drying reduces microbial activity and mineralization of organic C, N and P, decreases microbial mobility and restricts substrate and nutrient availability (West et al, 1992;Pulleman and Tietema, 1999). According to Magid et al (1999), microorganisms lose some of their ability to degrade complex substrates during desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…The main differences were higher abundances of both eukaryote and bacteria groups in habitats with surface water. This is supported in the literature where inundated stream sediments and soil have been shown to increase in bacterial biomass and activity (West et al 1992, Baldwin and Mitchell 2000, Austin and Strauss 2011, Wilson et al 2011 as well as increases in invertebrate assemblages (Larned et al 2007). In sediments with surface water, the higher abundances of eukaryotic groups were predominantly Gastrotricha, Ciliopora and Turbelaria as well as phototrophs such as the green alga Chlorophyta.…”
Section: Presence/absence Of Surface Watersupporting
confidence: 76%
“…The two dates coincide with variation in stream flow with the dry and wet season. Differences between the dry and wet season were expected as desiccation can be a stressor on microbial communities, where drying of stream sediments has been reported to affect ecosystem processes and change microbial community structure (West et al 1992, Boulding et al 2008, Marxsen et al 2009). The differences in community composition and consequences of changing hydrology in these sediments are further discussed in Section 6.4.1.…”
Section: Key Factors Influencing Microbial Communitiesmentioning
confidence: 99%